Tax Aggressiveness in Manufacturing Companies in Indonesia - Fuad Hasyim; Adhi Kresna Jiwayana (ITB AAS INDONESIA, 2021)
This study aims to analyze the factors that influence tax aggressiveness in manufacturing companies in Indonesia. This study uses a multiple linear regression approach using panel data. Data obtained from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange during 2015-2018 period. Sampling in this study was conducted by purposive sampling. The results of the study with the fixed effect approach show that the profitability variable has a significant effect on tax aggressiveness, while earnings management, leverage, and cash before the tax ratio have no effect.